АСПЕКТИ ПЕДАГОГІЧНОЇ КУЛЬТУРИ ЯК СКЛАДНОЇ ПРОФЕСІЙНОЇ КОМПЕТЕНТНОСТІ МАЙБУТНЬОГО ВЧИТЕЛЯ (Педагогіка вищої та середньої школи, 2022)
The article is dedicated to outhlook of pedagogical culture and its components as an important aspect of forming of future teacher’s professional authority.